Dukungan Sosial Orangtua, Regulasi Diri dan Prokrastinasi Akademik pada Siswa SMK Farmasi Depok - Dela Atfilah (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
This study aims to examine: (1) the influence between social support of parents and academic procrastination of Depok Pharmacy Vocational students, (2) the influence between self-regulation and academic procrastination on Depok Pharmacy Vocational students, and (3) the influence between social support of people old, self-regulation with academic procrastination. This study uses a correlational quantitative method. There are three scales used in this study, namely the scale of parental social support, the scale of self-regulation, and the scale of academic procrastination. Researchers used as many as 80 students of Depok Pharmacy Vocational School as a study sample selected using saturated sampling techniques. The data analysis technique used in this study is multiple linear regression test. The results of this study indicate that: (1) parental social support has a significant influence on academic procrastination with a negative relationship direction which can be seen from the significance value of 0,000 and the regression coefficient of -0.173. (2) self-regulation has a significant effect on academic procrastination with a negative relationship direction which can be seen from the significance value of 0,000 and the regression coefficient of -0,627. (3) Rsquare value of 0,481; it means that 48.1% of the variation in academic procrastination is influenced by parental social support and self-regulation, the remaining 51.9% is caused by other variables not measured in this study. The relationship between social support of parents and self-regulation with academic procrastination is known to have a significant relationship with a significance value of 0,000.